Field Building Leadership Initiative: Advancing Ecohealth in Southeast Asia - The first year journey - Hung Nguyen-Viet; Giang, H.P.; Tung, X.D. (Veterinary Public Health Centre for Asia Pacific, 2013)
The Ecosystem approach to health, or Ecohealth is a useful tool to address health and environmental issues in developing countries, particularly in South East Asia (SEA), where agricultural intensification processes have profound implications for ecosystems and health. The Field Building Leadership Initiative (FBLI) Advancing Ecohealth in SEA program aims to build the field of Ecohealth by integrating research, training, policy and networking to focus on solving human health problems associated with agricultural intensification in SEA countries. This paper aims at updating the one-year journey of the program from October 2011 until October 2012 and providing insights into the plan for the coming years. A number of activities of the project’s research component, capacity building, and knowledge translation have been completed in line with the proposal. Outcomes and outputs of the one-year implementation are also presented.